Neutrophil adhesion to endothelial cells and factors affecting adhesion in patients with Behcet's disease - DİRESKENELİ, RAFİ HANER (B M J PUBLISHING GROUP, 1996)
Objectives-To study the in vitro adhesion of polymorphonuclear leucocytes (PMNLs) to endothelial cells in patients with Behcet's disease (ED), and the humoral and cellular factors which may contribute to adhesion. Methods-A total of 118 patients with ED and 60 healthy controls were studied. In vitro adhesion of chromium-51 labelled normal neutrophils to human umbilical vascular endothelial cell (HUVEC) monolayers were studied in the presence of normal serum or serum obtained from patients with ED. Adhesion of neutrophils from patients with ED to HUVEC stimulated with tumour necrosis factor (TNF), interleukin-1 (IL-1), and lipopolysaccharide (LPS) and adhesion molecule (CD11a, CD11b, CD18 and L-selectin) expression on the patient's neutrophils and lymphocytes were determined, and the serum concentration of IL-8 was measured. Results-Sera from patients with ED were found to enhance the adherence of normal PMNLs to HUVEC monolayers in vitro. Patients' sera induced an increase in surface expression of CD11a and CD18 on normal neutrophils and intercellular adhesion molecule-1 (ICAM-1) expression on HUVECs. The number of CD11a positive neutrophils was greater in the blood of patients with ED than in that of healthy controls (89.4% v 71%; p < 0.001). Pretreatment of HUVECs with IL-1 alpha, TNF alpha or LPS resulted in an increased adhesion of patients' PMNLs greater than that observed for normal PMNLs. Monoclonal antibodies to CD11a, CD11b, CD18, and ICAM-1 caused varying degrees of inhibition of neutrophil adhesion. The concentration of IL-8 was also found to be significantly increased in sera of patients with ED (490 (SD 470) pg/ml) compared with normal controls (97.5 (56.3) pg/ml). Conclusion-Abnormalities of neutrophils, endothelial cells, or both, have been suggested to be responsible for many of the clinical manifestations of ED. Our findings may explain the underlying mechanism of neutrophil accumulation in Behcet's lesions.
Keywords: TUMOR-NECROSIS-FACTOR